Heavy Metals Pb In Water, Sediment And Shrimp Ghost Shrimp In The Coastal Subdistrict Labang, Bangkalan Madura - Abdul q j; Maria Kristiani (Journal of Aquaculture Development and Environment, 2018)
This study aims to determine the level of pollution in Madura Strait waters based on water quality parameters (pH, temperature, Dissloved Oxygen, and salinity), heavy metal Pb content in water, sediment and Ghost Shrimp as information on the importance of protecting the coastal environment from pollution. The method used is analysis of water quality (insitu) and sampling of water, sediment, Ghost Shrimp shrimp. As a bioindicator, the content of heavy metal Pb will be analyzed using AAS. The results of the water quality analysis found that the level of pollution in the Madura Strait, especially Labang Subdistrict, was included in the high category and was dangerous for the life of the organisms of the coastal ecosystem. This is because the western Madura strait is a waste disposal area from various major cities, such as Surabaya, Gresik, and Labang itself. Waste in the form of fuel spills for fishing boats, boat maintenance activities that use paint material. Household wastes and factories which are carried by current and suspended in the waters. Therefore, information on the dangers of consuming organisms that live and develop in the area of pollution becomes important for the health of coastal residents who depend on Madura strait marine resources.